Vitrinite reflectance and consolidation characteristics of the post‐middle Miocene Forearc Basin in central and eastern Boso Peninsula, central Japan: Implications for basin subsidence. (29th March 2020) - Kamiya, Nana; Yamamoto, Yuzuru; Zhang, Feng; Lin, Weiren
Abstract: To understand the sedimentary development of the Boso Forearc Basin, central Japan, since ~ 3 Ma, we investigated paleothermal structure and consolidation trends in the central and eastern parts of the forearc basin through vitrinite reflectance measurements and consolidation tests. Vitrinite reflectance (Rm ) was in the range 0.33 % to 0.61 % for the Miura Group in the central part of the forearc basin and 0.34 % to 0.41 % for the Miura and Kazusa Groups in the eastern. These values suggest a roughly uniform vitrinite reflectance for the Miura Group from the central to eastern parts. No significant vitrinite reflectance difference is observed across the ~ 3 Ma Kurotaki Unconformity in the eastern part of the basin. The consolidation yield stress ( p c ) was calculated as 27.5 MPa and 32.2 MPa for the Kiyosumi and Amatsu Formations of the Miura Group in the eastern part, respectively. Both the p c values are consistent quantitatively with represent the trend of the maximum overburden pressure estimated from the thickness and density of overlying sediments, and the difference in p c is expected by the maximum burial depths of the strata at the sampling localities. Values of p c in the eastern part of the basin increase with thickness of overlying sediment, showing no break across the Kurotaki Unconformity. Considering the eroded thickness of the Miura Group, the continuous trends in vitrinite reflectance and consolidation between the Miura and Kazusa Groups in the eastern part reflect the greater deposition of the eastern part of the Boso Forearc Basin since ~ 2.3 Ma.